Impacts of the Interannual Variability of the Kuroshio Extension on the East Asian Trough in Winter - Jianxiang Sun; Suping Zhang; Yuxi Jiang; Yanshuo Wang; Baoqin Wu; Haijiao Wang (Atmosphere, 2022)
The responses of the East Asian Trough (EAT) to the Kuroshio Extension (KE) interannual fluctuation and the underlying mechanisms in the boreal winter are investigated through the lag regression approach in this study. When the KE is in the stable state, the sea surface temperature (SST) front is strengthened, with cold (warm) SST anomaly in the western (eastern) region of the KE, releasing less (more) heat into the atmosphere. The opposite patterns hold for the KE unstable periods. The analysis of the observations shows that the stable KE corresponds to a deeper EAT, accompanied with a stronger winter monsoon over Mongolia and northeastern China. The atmospheric Rossby waves, transient eddies, and thermal winds are found to be responsible for this relationship between the KE and EAT. The SST warming in the lower reaches of the KE excites the Rossby wave activity that propagates toward East Asia, leading to 25% of the EAT amplification. Meanwhile, influenced by the KE-induced Rossby waves, the background baroclinicity is intensified over Japan, which enhances the transient eddy activity, contributing to another 42% magnitude of the EAT deepening. In addition, as depicted by the thermal wind theory, the strong SST cooling in the upper branch of the KE forces an anomalous cyclonic circulation through modifying the meridional temperature gradient, facilitating the EAT development. The finding points to the better understandings of the EAT and associated East Asian winter climate variability, which are crucial for their major economic and social impacts on the large populations in the region.